1995
DOI: 10.1111/j.1464-410x.1995.tb07260.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal piezoelectric shock wave lithotripsy as mono and multiple therapy of large renal calculi including staghorn stones in unanaesthetized patients under semi‐ambulant conditions

Abstract: We consider semi-ambulant EPL monotherapy to be a minimally invasive alternative treatment in patients with large renal calculi, including staghorn stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Many investigators believe that pre-ESWL JJ stenting of large renal stones helps to prevent obstruction and facilitates passage of fragments [8,21]. On the other hand Ryan et al [22] showed that in situ ureteric stents impair ureteric peristalsis and/or trap large fragments, thus delaying stone clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many investigators believe that pre-ESWL JJ stenting of large renal stones helps to prevent obstruction and facilitates passage of fragments [8,21]. On the other hand Ryan et al [22] showed that in situ ureteric stents impair ureteric peristalsis and/or trap large fragments, thus delaying stone clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In all studies that investigated the factors affecting ESWL outcome in management of large renal stones [7,8,9,10], a univariate analysis was only utilized, which does not take into account the possible interactions between the examined variables. To overcome this serious limitation, one has to resort to multivariate statistical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation